Evaluation of stiffness and damping of a base-isolated building considering higher-order modes - Tojo, Takaki; Suzuki, Takuya; Nakai, Shoichi (Frontiers in Built Environment, 2024)
Introduction: Structural health monitoring (SHM) is an effective method of understanding the seismic safety of seismic design models and the continued use of buildings after earthquakes. Various system identification methods applicable to SHM have been proposed; however, most target only superstructures. Their applicability for evaluating the soundness of foundations and soil structures should also be examined. In addition, evaluating high-order modes in addition to low-order modes is necessary to capture changes in the vibration characteristics of superstructures, foundations, and soil structures. However, the impact of considering higher-order modes on the identification results has not been sufficiently evaluated. This study aims to address these issues by clarifying the importance of considering higher-order modes and proposing a method that can contribute to improving the accuracy of future building health evaluation methods. Methods: This study proposes a method of evaluating the stiffness and damping of a superstructure and dynamic soil spring considering low-order to high-order modes using the efficient transfer function fitting system for a base-isolated (BI) building. First, numerical experiments were performed to examine the accuracy of the proposed method in evaluating the stiffness and damping of each part when using acceleration data from limited observation points. Furthermore, this method was applied to an existing BI building subjected to the 2011 off the Pacific Coast of Tohoku Earthquake (2011 Tohoku Earthquake) to identify each parameter while considering higher-order modes. In addition, secular changes and the amplitude dependence of each structure were analyzed.The results showed that the stiffness and damping of the seismic isolation layer, superstructure, and dynamic soil spring were stable with little variation owing to aging; however, the influence of amplitude dependence was relatively large.The significance of considering higher-order modes in evaluations of the soundness of foundations and soil structures was demonstrated. Moreover, the response characteristics of earthquakes recorded from 2007, before the 2011 Tohoku Earthquake, up to 2023 were accurately reproduced through numerical simulation by considering the amplitude dependence of the identified physical parameters based on the proposed identification framework.